Effect of Respiratory Muscles Training on Cardiopulmonary Parameters and Quality of Life in Patients with Dilated Cardiomyopathy - Suleman, Hanifa; Sheraz, Suman; Niaz, Aiman; Ghani, Hafiza Muriam; Ghafoor, Abdul; Rehman, Attiq Ur; Waris, Sadaf (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine effects of respiratory muscles training on cardiopulmonary parameters and quality of life in patients with dilated cardiomyopathy. Methodology: This Randomized Control Trial was conducted in Shifa International Hospital Islamabad from September 30, 2019 to December 31, 2019 and 22 patients with Dilated Cardiomyopathy were screened. Subjects were divided into 2 groups by sealed envelope sampling method. Bruce protocol according to ACSM guidelines (3 days per week, starting at shorter duration 5-20 min and progress to 30-40 min) was applied in Group 1. Bruce protocol same as in group 1 combined with Incentive spirometry (10-15 repetitions) and slow breathing technique was applied in Group 2. Tools and Outcome measures of study were EF, LV End systolic dimension, LV End diastolic dimension, QOL, PFT (FEV1, FVC, PEF and FEV1/FVC) and Vitals. Data was analyzed on SPSS version 21. Results: All patients in both groups were male with mean age of 51.65±6.5. Group 2 had improvement in LV End systolic dimension (pre training- 53.73+10.57, Post Training- 52.00+11.84), LV End diastolic dimension (pre training- 56.45+13.21, Post Training-55.45+14.08) as compared to Group 1 with LV End Systolic dimension ( pre training- 52.00+6.89, Post Training-51.56+6.71), LV End Diastolic dimension ( pre training- 60.00+6, Post Training-60.00+6.000). Conclusion: Respiratory muscles training by using bruce protocol combined with slow breathing and Incentive spirometry has significant effects on cardiopulmonary parameters and QOL in patients with dilated cardiomyopathy.